2018
DOI: 10.1007/s10853-018-2593-9
|View full text |Cite
|
Sign up to set email alerts
|

K x Na1−xNbO3 perovskite thin films grown by pulsed laser deposition on R-plane sapphire for tunable microwave devices

Abstract: K x Na 1-x NbO 3 thin films with x = 0.5 and x = 0.7 were deposited by pulsed laser deposition onto R-cut sapphire substrates to be suitable for microwave applications. The 500-800 nm-thick films present a preferential (100) orientation. The ω-scans show a weak mosaicity (full-width-athalf-maximum equal to 0.36° and 0.60° for x = 0.5 and x = 0.7, respectively). In addition to this texture, the in-plane ordering evidenced by X-ray diffraction φ-scan for the (100) orientation is in agreement with an epitaxial-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 41 publications
4
15
0
Order By: Relevance
“…Even though the literature does not present many microwave dielectric characterizations of the TTB phases, permittivity values close to 130 have also been reported for other materials [45,46]. Nevertheless, these values remain lower than those retrieved from the K x Na 1-x NbO 3 perovskite phase in the same settings [47]. The dielectric permittivity decrease of the TTB phase from ε r ≈ 200 at low frequency to ε r ≈ 130 at high frequency is consistent with the decrease as reported in the literature.…”
Section: High Frequency Measurementsmentioning
confidence: 78%
See 1 more Smart Citation
“…Even though the literature does not present many microwave dielectric characterizations of the TTB phases, permittivity values close to 130 have also been reported for other materials [45,46]. Nevertheless, these values remain lower than those retrieved from the K x Na 1-x NbO 3 perovskite phase in the same settings [47]. The dielectric permittivity decrease of the TTB phase from ε r ≈ 200 at low frequency to ε r ≈ 130 at high frequency is consistent with the decrease as reported in the literature.…”
Section: High Frequency Measurementsmentioning
confidence: 78%
“…Table 2 gathers the deposition parameters of the films considered in the present study. Since a film thickness of about 250 nm was obtained with the laser frequency of 2 Hz, the frequency was increased to 4 Hz to achieve a thickness near 500 nm, more suitable for the high frequency reconfigurable devices [47].…”
Section: Influence Of the Deposition Parameters To Grow Pure Knn Ttb mentioning
confidence: 99%
“…KNN‐based epitaxial films have also drawn attention in some practical applications due to the characteristics different from polycrystalline films as well as bulk ceramics. Researchers have investigated KNN‐based epitaxial films for optical application, surface acoustic wave (SAW) devices, and tunable microwave devices, taking advantage of the manipulated lattice strain, the anisotropy strain, and electric properties in the epitaxial films.…”
Section: Epitaxial Filmsmentioning
confidence: 99%
“…[21]) with a Curie temperature close to 400°C [22], making it a promising alternative to the widely used PbZrTiO3 material. In addition, recent studies have also demonstrated interesting KNN thin films properties at microwaves with a high dielectric constant (r  360 at 10 GHz and 22%-frequency tunability under 94 kV/cm dc bias electric field [23], [24]).…”
Section: Introductionmentioning
confidence: 98%